Ten years of research on bioactive peptides in Brazil: a scientometric analysis - SILVA, Edson Flávio Teixeira da (2023)
Peptides are biomolecules composed of amino acids linked through peptide bonds present in proteins. These peptides may have biological activities associated with their secondary structure, especially when released from the original protein sequence. The prospect of these biomolecules is the subject of study and research in various sectors, including the food and pharmaceutical industries. This is due to the possibility of using them as substitutes for traditionally marketed drugs, especially those with restrictive legislation on their use, or losing their effectiveness. A scientometric analysis of studies published from 2011 to 2021 by Brazilian researchers demonstrated the growing interest in basic research involving bioactive peptides from numerous protein sources, including food-based and agro-industrial residues. The antioxidant activity, followed by the antimicrobial potential, has been the most studied property of these biomolecules. Several other activities such as anxiolytic, anti-adipogenic, anticoagulant, anticonvulsant, antisclerotic, and cytoregulatory actions have been reported in a limited number of studies, highlighting the potential application of these biomolecules in the development of new products.